HUBUNGAN FAKTOR PERSONAL DAN PEKERJAAN DENGAN PERILAKU BERBAHAYA PADA PEKERJA PROYEK TOL CINERE - JAGORAWI SEKSI 3 PT PP PRESISI TBK - Andika Fajar Hidayatulloh, (2023)
The construction industry is the most significant contributor to work accidents in Indonesia, with an average incidence of around 32% annually. The dominant cause of work accidents is unsafe actions. There are findings of unsafe action in the Cinere - Jagorawi Toll Road Project Section 3, such as not using personal protective equipment and working with improper body position. This study aimed to determine the association between personals and job factors with unsafe actions in Cinere - Jagorawi Toll Project workers Section 3 PT PP Presisi Tbk. The research method used was quantitative with a cross-sectional study design. The sampling technique employed was total sampling, with a sample size of 90 workers. The research instruments used were questionnaires and observation sheets, and the statistical test used was the chi-square test. The analysis showed that there was a significant association between personal factors, including knowledge (p-value=0,000), training (p-value=0,022), work stress (p-value=0,007), and motivation (p-value=0,010) with unsafe actions. As for job factors, there was a significant association between supervision (p-value=0,019) with unsafe acts. It is suggested that companies provide education related to dangerous behavior and conduct refresher programs before work, implement reward and punishment policies, and increase the frequency of supervision.